Evaluación de la capacidad de sorción de cromo en solución acuosa en contacto con un composite constituido de bentonita y celulosa - Novillo Kuonqui, María Isabel (2015)
The present study aims to assess the sorption capacity of chromium (VI) in different aqueous solutions, using a composite consisting of bentonite and cellulose in different ratios. The investigation began with the obtention of sorbents: pinzontes rachis banana (Musa paradisiaca L.), lawn (Pennisetum clandestinum) and calcium bentonite (clay material); subsequently, the rachis, lawn and calcium bentonite were modified by acid digestion. Later the modification was analyzed by infrared spectrophotometry. Three different types of matrices (natural and modified) that consisted of calcium bentonite and cellulose (lawn and banana rachis) were developed in a ratio of 2: 1; 1: 1 and 1: 2, respectively; through agitation at various times these samples were in contact with chromium solutions prepared at different concentrations. The samples were adjusted to a predetermined optimum pH and were examined by atomic absorption spectrophotometry. After the investigation, it was observed that the best matrix used was the CN (natural composite) in a ratio of 1: 1 clay-cellulose, where the retention capacity of metals was analyzed as a function of pH and time, being for chromium the optimum pH between 3 and 5. The maximum retention of metal in the matrix (CN 1: 1) (Qmax), which value was 145.3 mg chromium/natural sorbent, was calculated in the isothermal study. The results allow concluding that natural and modified sorbents have good sorption capacity.